Lithium metal battery
By adding specific compounds to the electrolyte of lithium metal batteries and controlling their component ratio, combined with the optimization of the membrane and the adjustment of the electrolyte components, the problem of unsatisfactory circulation stability of lithium metal batteries at low temperatures is solved, and better cycle life and safety performance are achieved.
Patent Information
- Application Number
- CN202411873286.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-12-18
AI Technical Summary
Lithium metal batteries have problems with safety and low-temperature cycling performance during charging and discharging, especially the existing electrolyte system has poor circulation stability at low temperatures.
By adding compound A and compound B to the electrolyte, and controlling its mass proportion and liquid retention coefficient in the electrolyte, the optimized separator structure and electrolyte components, including phosphorus and nitrogen-containing compounds, are combined to improve the cycle stability and safety performance of the battery.
It realizes the low-temperature and room-temperature circulation performance of lithium metal batteries while ensuring safety performance, extends the cycle life of the battery, and improves the safety of the battery.
Smart Images

Figure BDA0005196247110000022 
Figure BDA0005196247110000023 
Figure BDA0005196247110000025
Abstract
Description
Technical Field
[0001] The present invention relates to the field of battery materials, and in particular to a lithium metal battery. Background Art
[0002] Lithium metal batteries are considered an important candidate for the next generation of high energy density batteries due to their extremely high theoretical energy density (far exceeding the current mainstream lithium-ion batteries). However, the current development of lithium metal batteries still faces many challenges. Metallic lithium is highly reactive and easily reacts with components in the electrolyte, resulting in a large amount of heat and gas generated inside the battery. At the same time, during the charging and discharging process, the uneven deposition of lithium will form lithium dendrites, which may penetrate the diaphragm, causing a short circuit inside the battery, and may also cause serious consequences such as overheating, fire, and even explosion.
[0003] Regarding the above safety issues, relevant technical reports disclose that an electrolyte system with better compatibility with lithium metal can be developed to improve the cycle life and safety of the battery. However, the current public electrolyte system, while ensuring safety, does not have ideal battery cycle stability, especially low-temperature cycle stability. Therefore, existing lithium metal batteries have the problem of not being able to take into account both safety and low-temperature cycle performance at the same time. Summary of the invention
[0004] The present invention provides a lithium metal battery, aiming to improve the low-temperature and normal-temperature cycle performance on the basis of ensuring the safety performance of the lithium metal battery.
[0005] The present invention provides a lithium metal battery, comprising an electrolyte, a separator, a positive electrode sheet, and a negative electrode sheet, wherein the electrolyte comprises a compound A and a compound B;
[0006] The mass proportion of the compound A in the electrolyte is a%, and a satisfies: 5≤a≤50;
[0007] The mass proportion of the compound B in the electrolyte is b%, and b satisfies: 5≤b≤50;
[0008] The liquid retention coefficient of the lithium metal battery is zg / Ah, and z satisfies: 1.5≤z≤2.2;
[0009] The compound A comprises at least one of the structures shown in Formula 1,
[0010] Formula 1: Wherein, R1 and R2 are independently selected from H, halogen, halogen-substituted or unsubstituted hydrocarbon group with 1 to 6 carbon atoms, and hydrocarbonoxy group;
[0011] The compound B comprises at least one of the structures shown in Formula 2,
[0012] Formula 2: Wherein, R3 and R4 are independently selected from H, F substituted or unsubstituted hydrocarbon groups and hydrocarbonoxy groups with 1 to 10 carbon atoms, and at least one of R3 and R4 contains F.
[0013] The compound A includes at least one of the following structural formulas 1-1 to 1-8:
[0014]
[0015] And / or, the compound B comprises at least one of the following structural formulas 2-1 to 2-8:
[0016]
[0017] As a preferred configuration, the lithium metal battery satisfies: 13≤(a+b) / z≤40.
[0018] As one of the configurations, the electrolyte further includes a compound F, and the compound F includes at least one of the structures shown in Formula 3,
[0019] Formula 3: Wherein, R5 and R6 are independently selected from a hydrocarbon group or a hydrocarbonoxy group having 1 to 10 carbon atoms;
[0020] Preferably, compound F accounts for f% of the total mass of the electrolyte, and f satisfies: 10≤f≤20;
[0021] Preferably, the compound F comprises at least one of the following structural formulas 3-1 to 3-8:
[0022]
[0023]
[0024] As one of the configurations, the diaphragm includes a base layer and a glue layer disposed on the surface of the base layer; the thickness of the glue layer is d μm, and d satisfies: 0.5≤d≤8.
[0025] The base layer includes a substrate layer and a ceramic layer located on one side or both sides of the substrate layer; preferably, the thickness of the ceramic layer is e μm, and e satisfies: 0<e≤8.
[0026] The ceramic layer includes inorganic particles, the particle size of the inorganic particles is g μm, and g satisfies: 0.1≤g≤1.5;
[0027] And / or, the porosity of the separator is h%, where h satisfies: 30≤h≤50.
[0028] As one of the configurations, the electrolyte further contains a phosphorus-containing compound;
[0029] Preferably, the phosphorus-containing compound accounts for i% of the total mass of the electrolyte, and i satisfies: 0.1≤i≤20;
[0030] More preferably, the phosphorus-containing compound is selected from at least one of LiPO2F2, tris(2,2,2-trifluoroethyl) phosphate, triphenyl phosphate, ethoxypentafluorocyclotriphosphazene, triphenyl phosphine oxide, triphenyl phosphine, p-toluoyl phosphate, and toluene diphenyl phosphate.
[0031] As one of the configurations, the electrolyte also includes a nitrogen-containing compound;
[0032] Preferably, the nitrogen-containing compound accounts for j% of the total mass of the electrolyte, and j satisfies: 0.1≤j≤5;
[0033] Preferably, the nitrogen-containing compound is selected from one or more of lithium nitrate, 2-fluoropyridine, pentafluoropyridine, 3-fluoropyridine, 2-trimethylsilylethynylpyridine, 1,2-bis(di-2-pyridylphosphine)ethane, 1-methylbenzotriazole, isopropyl nitrate, and 4-ethylpyridine.
[0034] As one of the configurations, the positive electrode sheet includes a positive electrode active material, and the positive electrode active material includes a ternary material;
[0035] Preferably, the lithium metal battery is a laminated battery.
[0036] The technical solution of the present invention has the following advantages:
[0037] A lithium metal battery provided by the present invention includes a compound A with lower density and viscosity in the electrolyte, and a compound B used to reduce the flammability of the electrolyte to cooperate with each other to ensure the safety of the battery; at the same time, compound A does not participate in the solvation structure, and will promote the film formation of the negative electrode, reducing the continuous consumption of solvents and lithium salts; therefore, the lithium metal battery of the present invention can be controlled by controlling the liquid retention coefficient within a smaller value range, and the comprehensive regulation of the content of compound A and compound B can ensure that it has a higher safety performance and has an excellent cycle life. In particular, by controlling (a+b) / z within the range of 13-40, a more excellent cycle life, especially a low-temperature cycle life, can be obtained.
[0038] Additional aspects and advantages of embodiments of the present invention will be described and shown in part in the following description, or will be explained through the implementation of embodiments of the present invention. DETAILED DESCRIPTION
[0039] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.
[0040] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.
[0041] In addition, the technical features involved in the different embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0042] The present invention provides a lithium metal battery, comprising an electrolyte, a separator, a positive electrode sheet, and a negative electrode sheet, wherein the electrolyte comprises a compound A and a compound B;
[0043] The mass proportion of the compound A in the electrolyte is a%, and a satisfies: 5≤a≤50;
[0044] The mass proportion of the compound B in the electrolyte is b%, and b satisfies: 5≤b≤50;
[0045] The liquid retention coefficient of the lithium metal battery is zg / Ah, and z satisfies: 1.5≤z≤2.2;
[0046] The compound A comprises at least one of the structures shown in Formula 1,
[0047] Formula 1: Wherein, R1 and R2 are independently selected from H, halogen, halogen-substituted or unsubstituted hydrocarbon group with 1 to 6 carbon atoms, and hydrocarbonoxy group;
[0048] The compound B comprises at least one of the structures shown in Formula 2,
[0049] Formula 2: Wherein, R3 and R4 are independently selected from H, F substituted or unsubstituted hydrocarbon groups and hydrocarbonoxy groups with 1 to 10 carbon atoms, and at least one of R3 and R4 contains F.
[0050] The test method of the liquid retention coefficient in the present invention is as follows: first test the battery capacity D (conventional methods can be used for testing), disassemble the battery to be disassembled, pour out the free electrolyte and weigh M1, then extract the shell three times with M mass of dimethyl carbonate (DMC), pour out the DMC residual liquid and weigh M2; weigh the weight M3 of the electrode assembly and the shell at this time, then put it into an oven for baking, weigh the mass M4 of the electrode assembly and the shell after drying, use M1+M2+M3-M4-M to obtain the amount of electrolyte m in the battery, and then use m / D as the liquid retention coefficient of the battery.
[0051] Because the electrolyte of conventional lithium metal batteries is denser than that of ordinary lithium-ion electrolytes, and the electrolyte will continuously participate in film formation during the circulation process, which leads to faster consumption of the electrolyte, it is usually necessary to control the initial liquid retention coefficient of lithium metal batteries to a higher level to ensure the cycle performance. The liquid retention coefficient of conventional lithium metal batteries needs to be controlled to 4.3~5.0g / Ah. In the electrolyte of the present invention, since compound A can significantly reduce the overall viscosity of the electrolyte, at low temperatures, the low viscosity of the electrolyte is conducive to the migration of lithium ions in the electrolyte, improves the conductivity of the electrolyte, and thus improves the low-temperature cycle performance of the battery; at the same time, compound A also has a smaller maximum electrostatic potential energy, is not easy to destroy the ion-solvent interaction in the solvation layer, and does not participate in the solvation structure of lithium ions, promotes negative electrode film formation, and effectively reduces the continuous consumption of solvents, lithium salts, and anions during the charging and discharging process. Therefore, compound A can reduce the consumption of solvents participating in the solvation structure during the cycle. The present invention only needs to control a smaller liquid retention coefficient z to cooperate with the compound A to have an excellent cycle life, especially a low-temperature cycle life; and it can also prevent the electrolyte from easily undergoing side reactions when the liquid retention coefficient is high, generating gas, and causing the internal pressure of the battery to increase, so that it may have safety problems such as battery expansion, leakage, and even explosion during charging and discharging, thereby improving the safety performance of the battery. However, compound A is highly flammable. When a lithium metal battery is micro-shorted due to dendrite growth, it will cause serious safety problems. In order to reduce the flammability of the electrolyte, the electrolyte of the present invention also contains compound B. The viscosity and density of compound B are greater than those of compound A. Although the effect of compound B in improving the cycle performance of the battery in the electrolyte is not as good as compound A, compound B itself is non-flammable. Through the mutual cooperation of compound A and compound B in the electrolyte, the flammability of the electrolyte can be reduced, the battery fire and explosion when the battery is micro-short-circuited can be suppressed, and the battery safety performance can be improved.
[0052] In summary, the present invention comprehensively controls the relationship between compound A, compound B and the liquid retention coefficient z so that when the conditions of 5≤a≤50, 5≤b≤50, and 1.5≤z≤2.2 in the present invention are satisfied, the battery of the present invention can maintain good cycle stability and good safety performance within the range of the liquid retention coefficient, and in particular, can effectively improve the low-temperature and room-temperature cycle performance while ensuring safety.
[0053] As an example, the mass proportion a% of compound A in the electrolyte can be 5%, 10%, 20%, 30%, 40%, 50% or in the range of any two of the above values; the mass proportion b% of compound B in the electrolyte can be 5%, 10%, 20%, 25%, 30%, 35%, 40%, 45%, 50% or in the range of any two of the above values; the liquid retention coefficient zg / Ah of the lithium metal battery can be 1.5g / Ah, 1.6g / Ah, 1.7g / Ah, 1.8g / Ah, 1.9g / Ah, 2.0g / Ah, 2.1g / Ah, 2.2g / Ah or in the range of any two of the above values.
[0054] In an optional embodiment, the compound A comprises at least one of the following structural formulas 1-1 to 1-8:
[0055]
[0056] Preferably, the compound A of the present invention is a para-substituted structure, the interaction between the two substituents is weak, the effect on the electron cloud density of the benzene ring is small, which is conducive to maintaining the stability of the benzene ring. In the electrolyte, the benzene ring is not easily decomposed and opened, so that the compound A can form a more stable, LiF-rich protective film on the electrode surface, which can not only prevent further reaction between the electrolyte and the electrode material, but also reduce the battery interface impedance and improve the battery cycle performance.
[0057] The number of F atoms in the compound B is ≥4;
[0058] Preferably, the compound B comprises at least one of the following structural formulas 2-1 to 2-8:
[0059]
[0060] In an optional implementation, 13≤(a+b) / z≤40 is controlled, under which condition better safety performance and cycle stability can be achieved.
[0061] As an example, (a+b) / z may be 13, 15, 17, 19, 20, 25, 30, 35, 40, or a range consisting of any two of the above values.
[0062] In an optional embodiment, the electrolyte further includes compound F, which accounts for f% of the total mass of the electrolyte, and f satisfies: 10≤f≤20; the number of fluorine atoms in compound F is less than 4, preferably ≤2; since fluorinated ethers with fluorine atoms ≥4 do not dissolve lithium salts, in order to improve the solubility of lithium salts and increase the lithium salt content in the electrolyte, the present invention further adds an ether compound F with fluorine atoms less than 4 to solvate the lithium salt, thereby improving the cycle performance.
[0063] The compound F of the present invention comprises at least one of the structures shown in Formula 3,
[0064] Formula 3: Wherein, R5 and R6 are independently selected from hydrocarbon groups and hydrocarbonoxy groups having 1 to 10 carbon atoms.
[0065] The compound F in the electrolyte of the present invention is a non-fluorinated ether compound. The compound F not only has good compatibility with lithium metal and is not prone to side reactions, but also has better wetting ability than ordinary carbonate solvents, can fully infiltrate into the interior of the electrode material, improve the utilization rate of the active material, and can further improve the cycle performance and safety performance.
[0066] Preferably, compound F accounts for f% of the total mass of the electrolyte, and f satisfies: 10≤f≤20; as an example, the mass proportion of compound F in the electrolyte may be 10%, 12%, 14%, 16%, 18%, 20%, or within the range of any two of the above values;
[0067] Preferably, the compound F comprises at least one of the following structural formulas 3-1 to 3-8:
[0068]
[0069] In an optional embodiment, the diaphragm includes a substrate layer and a glue layer arranged on the surface of the substrate layer; the thickness of the glue layer is d μm, and d satisfies: 0.5≤d≤8.
[0070] The diaphragm of the present invention has a glue layer with a thickness of dμm, which enables the positive and negative electrodes and the diaphragm to be tightly bonded together, reducing the transmission distance of lithium ions, improving the ion transmission efficiency, and further improving the low-temperature cycle performance of the lithium-ion battery; and because the positive and negative electrodes and the diaphragm are tightly bonded, lithium ions will be directly embedded in the negative electrode after passing through the microporous structure of the diaphragm, and the pore size and pores of the diaphragm are evenly distributed. Therefore, through the optimized setting of the diaphragm, lithium ions can be evenly deposited, reducing the situation of lithium plating, and further improving the safety performance of the lithium-ion battery.
[0071] As an example, the thickness d μm of the glue layer may be 0.5 μm, 0.8 μm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm or a range formed by any two of the above values.
[0072] In an optional embodiment, the base layer includes a substrate layer and a ceramic layer located on one side or both sides of the substrate layer; preferably, the thickness of the ceramic layer is e μm, and e satisfies: 0<e≤8.
[0073] The ceramic layer in the diaphragm described in the present invention can enhance the mechanical strength of the diaphragm, improve its tensile strength, puncture resistance and other capabilities, prevent the diaphragm from being easily punctured to cause a battery short circuit, and further improve the safety performance of the battery.
[0074] As an example, the thickness eμm of the ceramic layer may be 0.1μm, 0.5μm, 0.8μm, 1μm, 2μm, 3μm, 4μm, 5μm, 6μm, 7μm, 8μm or a range formed by any two of the above values.
[0075] In an optional embodiment, reducing the ceramic particle size can enhance the mechanical strength of the diaphragm and improve the situation where the electrolyte scours and destroys the diaphragm structure. The particle size of the ceramic layer is gμm, and g satisfies: 0.1≤g≤1; the particle size range of the ceramic layer in the diaphragm of the present invention is relatively small, which can not only provide a denser ion transmission channel, improve the ion transmission efficiency, and reduce the internal resistance of the battery; it can also increase the contact area between the diaphragm and the electrolyte, and increase the diffusion rate of lithium ions, thereby improving the cycle performance of the battery, especially the low-temperature cycle performance. And under high temperature conditions, nano-scale ceramic particles can also inhibit the thermal shrinkage and deformation of the diaphragm, maintain the integrity of the battery structure, and prevent the occurrence of safety problems such as thermal runaway, thereby improving safety.
[0076] As an example, the particle size of the ceramic layer may be 0.1 μm, 0.2 μm, 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1.0 μm, 1.1 μm, 1.2 μm, 1.3 μm, 1.4 μm, 1.5 μm or within a range formed by any two of the above values.
[0077] In an optional embodiment, the diaphragm of the present invention has a larger porosity, which can provide more channels for ion transmission, reduce the internal resistance of the battery, thereby improving the ion conductivity of the battery, and improve the cycle performance of the battery, but the high porosity may cause direct contact between the positive and negative electrodes or lithium dendrites to penetrate the diaphragm; the porosity of the diaphragm in the present invention is h%, and h satisfies: 30≤h≤50.
[0078] As an example, the porosity h% of the separator may be 30%, 35%, 40%, 45%, 50% or a range formed by any two of the above values.
[0079] In an optional embodiment, the electrolyte further contains a phosphorus-containing compound, and the phosphorus-containing compound accounts for i% of the total mass of the electrolyte, and i satisfies: 0.1≤i≤20.
[0080] The phosphorus-containing additive in the electrolyte of the present invention can form a complex with the metal elements in the positive electrode material of the battery, further maintaining the structural stability of the electrode material during the cycle and improving the cycle life; at the same time, the phosphorus-containing compound can further reduce the flammability of the electrolyte, improve the thermal stability of the electrolyte, and make the battery less prone to thermal runaway even if a short circuit occurs.
[0081] As an example, the phosphorus-containing compound may account for i% of the total mass of the electrolyte, which may be 0.1%, 0.5%, 1%, 3%, 5%, 7%, 10%, 12%, 15%, 18%, 20% or a range formed by any two of the above values.
[0082] More preferably, the phosphorus-containing compound is selected from at least one of LiPO2F2, tris(2,2,2-trifluoroethyl) phosphate, triphenyl phosphate, ethoxypentafluorocyclotriphosphazene, triphenyl phosphine oxide, triphenyl phosphine, p-toluoyl phosphate, and toluene diphenyl phosphate;
[0083] In an optional embodiment, the electrolyte further includes a nitrogen-containing compound, the nitrogen-containing compound accounts for j% of the total mass of the electrolyte, and j satisfies: 0.1≤j≤5.
[0084] The nitrogen-containing compound in the present invention can promote the formation of a Li3N-containing SEI film at the negative electrode, which can not only improve the elasticity and mechanical strength of the SEI film, but also form a conductive channel, so that lithium ions can migrate more easily through the SEI film. This high conductivity helps to reduce the transmission resistance of lithium ions in the SEI film, thereby increasing the conduction of lithium ions, allowing lithium ions to pass through the SEI film more quickly, reducing the accumulation and blockage of lithium ions in the SEI film, thereby improving the charge and discharge efficiency and cycle stability of the battery.
[0085] As an example, j% of the total mass of the electrolyte containing nitrogen compounds can be 0.1%, 0.3%, 0.5%, 0.7%, 0.9%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5% or within the range of any two of the above values.
[0086] Preferably, the nitrogen-containing compound is selected from one or more of lithium nitrate, 2-fluoropyridine, pentafluoropyridine, 3-fluoropyridine, 2-trimethylsilylethynylpyridine, 1,2-bis(di-2-pyridylphosphine)ethane, 1-methylbenzotriazole, isopropyl nitrate, and 4-ethylpyridine.
[0087] In an optional embodiment, the lithium salt described in the electrolyte of the present invention may include at least one of lithium hexafluorophosphate (LiPF6), lithium difluorophosphate (LiPO2F2), lithium difluorooxalatoborate (LiDFOB), lithium bis(trifluoromethylsulfonyl)imide (LiFSI), lithium bis(trifluoromethylsulfonyl)imide (LiTFSI), lithium difluorobis(oxalatophosphate), lithium tetrafluoroborate, lithium bis(oxalatoborate), lithium hexafluoroantimonate, lithium hexafluoroarsenate, lithium bis(pentafluoroethylsulfonyl)imide, tris(trifluoromethylsulfonyl)methyl lithium and lithium bis(trifluoromethylsulfonyl)imide.
[0088] In an optional embodiment, the positive electrode sheet includes a current collector and a positive electrode active material layer disposed on the surface of the current collector, and the positive electrode active material layer includes a positive electrode active material, a conductive agent and a binder.
[0089] Preferably, the positive electrode active material in the positive electrode sheet is a ternary material.
[0090] In an optional embodiment, the chemical structure of the ternary material is preferably LiNi x Co y Mn z O2, wherein x+y+z=1, and also includes doping coating elements: one or more of Al, Zr, Mg, Y, Ti, B, Sr, W, Si, La, Nb and the like, wherein the total amount of Al+Mg+Zr is 1000-16000ppm, wherein the particle size Dv50 of the single crystal particles in the ternary material is 1-6μm.
[0091] As an example, the total amount of Al+Mg+Zr may be 1000 ppm, 3000 ppm, 5000 ppm, 8000 ppm, 10000 ppm, 13000 ppm, 16000 ppm or a range consisting of any two of the above values.
[0092] As an example, the particle size Dv50 of the single crystal particles in the ternary material can be 1μm, 1.5μm, 1μm, 2μm, 2.5μm, 3μm, 3.5μm, 4μm, 5μm, 6μm or a range consisting of any two of the above values.
[0093] The ternary material in the present invention has better thermal stability than other positive electrode active materials (such as lithium cobalt oxide), can maintain structural stability under high temperature conditions, and reduce the risk of thermal runaway; therefore, the positive electrode material in the present invention is selected as a ternary material. At the same time, the ternary material has a good cycle life and can withstand a long-term cycle charge and discharge process without prone to capacity decay. The use of ternary materials in the present invention can further improve the cycle performance and safety performance.
[0094] The type of conductive agent used in the positive electrode sheet is not particularly limited in the present invention, and it can be selected from the conductive agents commonly used in the art, including but not limited to one or more of acetylene black, conductive carbon black, Ketjen black, conductive graphite, carbon nanotubes, conductive carbon fibers, and graphene;
[0095] The present invention does not particularly limit the type of binder used in the positive electrode sheet, which can be selected from binders conventionally used in the art, including but not limited to one or more of polyvinylidene fluoride, polytetrafluoroethylene, sodium carboxymethyl cellulose, styrene-butadiene rubber, and polyethylene oxide.
[0096] The negative electrode sheet of the present invention includes a current collector and a negative electrode active material layer disposed on the surface of the current collector. The active material of the negative electrode active material layer can be selected from lithium metal, and the current collector of the negative electrode sheet can be selected from copper foil in the art. The negative electrode active material layer also includes a conductive agent and a binder. The present invention does not specifically limit the types of the conductive agent and the binder in the negative electrode sheet. The selection range can refer to the types of the conductive agent and the binder in the positive electrode sheet, and will not be repeated here.
[0097] The negative electrode sheet of the present invention can be prepared by the following method: lithium alloy and copper foil of a certain thickness are selected, rolled under a certain pressure and then cut into pieces to obtain lithium metal negative electrode sheets, and then dried to obtain the negative electrode sheets.
[0098] In an optional embodiment, the lithium metal battery is a battery with a laminate structure. The laminate structure design enables the lithium metal battery to dissipate heat better, reduces the problem of stress concentration, has higher mechanical stability, and is easier to avoid the risk of battery short circuit than the winding structure. In addition, the laminated battery has fewer thermal runaway and overheating problems, so it is safer.
[0099] The present invention does not specifically limit the preparation method of the lithium-ion battery, and the lithium-ion battery can be prepared by conventional preparation methods in the art. For example, the positive electrode sheet, the separator and the negative electrode sheet are stacked in sequence, so that the separator is located between the positive electrode sheet and the negative electrode sheet, and the battery core is obtained through the stacking process, and then the lithium-ion battery of the present invention is obtained through the processes of baking, liquid injection, formation, packaging, etc.
[0100] In an optional embodiment, based on the design of the battery volume, the number of stacking sheets x of the negative electrode sheets in the stacking structure within the same volume is further optimized to give full play to the high energy density advantage of lithium metal batteries. Specifically, in order to give full play to the high energy density advantage of lithium metal batteries, the number of stacking sheets of the positive and negative electrodes of the battery should be increased as much as possible during the design and preparation of the battery. However, as the number of negative electrode sheets increases, the contact area between the negative electrode sheets and the electrolyte will also increase, the side reactions will also increase, and the growth of lithium dendrites will also intensify, which will affect the safety performance; during the charging and discharging process of the battery, the volume of the lithium metal negative electrode changes greatly. When the number of negative electrode sheets increases, the battery volume change rate will also increase significantly. The great stress is also easy to cause the battery shell to rupture, resulting in problems such as electrolyte leakage, thereby affecting the safety performance; therefore, the number of negative electrode sheets x in the present invention can be increased without greatly affecting the safety performance. For the stacked batteries with the design requirements listed in the following embodiments, the number of negative electrode sheets x can meet 10<x≤25. As an example, the number of negative electrode sheets is x sheets, which can be 10 sheets, 12 sheets, 14 sheets, 16 sheets, 18 sheets, 20 sheets, 22 sheets, 24 sheets, 25 sheets, or a range between any two of the above values.
[0101] The present invention is further described in detail below in conjunction with specific examples, which should not be construed as limiting the scope of the invention. In all examples and comparative examples of the present invention, the unit wt% represents mass percentage.
[0102] Example 1
[0103] A lithium metal battery, the preparation process of which is as follows:
[0104] (1) Preparation of positive electrode
[0105] The positive electrode active material (NCM811), polyvinylidene fluoride, conductive carbon black and carbon nanotubes were mixed in a mass ratio of 96:2:1.5:0.5, N-methylpyrrolidone (NMP) was added, and the mixture was stirred under the action of a vacuum mixer until the mixed system became a positive electrode active slurry with uniform fluidity; the positive electrode active slurry was evenly coated on both surfaces of the aluminum foil; the coated aluminum foil was dried, and the desired positive electrode sheet was obtained by rolling and slitting, wherein the surface density of the positive electrode sheet was 3.5 mAh / cm 2 .
[0106] (2) Preparation of negative electrode sheet
[0107] The lithium metal was compounded onto the copper foil by a physical roller pressing method. The roller pressure was adjusted so that the copper foil was coated with lithium alloy on both sides and the thickness of the lithium alloy on one side was controlled to be about 30 μm (i.e., the thickness of the negative electrode active material layer on one side was about 30 μm). After cutting and slitting, the negative electrode sheet was obtained and placed in a dry argon atmosphere glove box for storage. The surface density of the negative electrode sheet was 5 mAh / cm 2 .
[0108] (3) Preparation of electrolyte
[0109] In a glove box filled with argon (H2O<0.1ppm, O2<0.1ppm), 30% of lithium salt (LiFSI) based on the total mass of the electrolyte was added to compound F based on the total mass of the electrolyte, dissolved and stirred evenly, a% of compound A and b% of compound B based on the total weight of the electrolyte were added, and then 5% of the phosphorus-containing compound (ethoxypentafluorocyclotriphosphazene) based on the total mass of the electrolyte was added, and finally 1% of the nitrogen-containing compound (lithium nitrate) based on the total mass of the electrolyte was added to obtain an electrolyte. The specific addition amounts and types are shown in Table 1.
[0110] (4) Obtaining the diaphragm
[0111] A layer of glue is coated on the ceramic diaphragm to obtain a polyethylene film with a glue layer thickness of 1 μm, a ceramic layer thickness of 2 μm, a ceramic layer particle size of 0.5 μm, and a porosity of 40%. The specific parameter settings are shown in Table 1 below;
[0112] Table 1
[0113]
[0114]
[0115] The compounds with structures shown in the above table are all currently commercially available products.
[0116] (5) Preparation of batteries
[0117] The positive electrode sheet prepared in step (1), the negative electrode sheet prepared in step (2) and the separator prepared in step (4) are stacked in the order of positive electrode sheet, separator, negative electrode sheet and separator, with the number of stacked negative electrode sheets being 20, to obtain a battery cell; the battery cell is placed in an outer packaging aluminum foil, the electrolyte prepared in step (3) is injected into the outer packaging aluminum foil, and a lithium metal battery is obtained through vacuum packaging, standing, forming, shaping, sorting and other processes.
[0118] The battery prepared by the process of the present invention has a charge and discharge range of 3.0-4.25V.
[0119] Example 2
[0120] A lithium metal battery, which differs from Example 1 in that the content a% of compound A, the content b% of compound B, the content f% of compound F, the content c% and type of lithium salt, the content i% and type of phosphorus-containing compound, and the content j% and type of nitrogen-containing compound are different, and other parameter conditions not shown are exactly the same as those of Example 1-1, and the specific settings are shown in Table 2 below:
[0121] Table 2
[0122]
[0123]
[0124] Other parameter conditions not shown are exactly the same as those in Example 1-1, and the compounds with structures shown in the above table are all existing commercially available products.
[0125] Example 3
[0126] A lithium metal battery, which is different from Example 1 in that the parameter settings in the diaphragm are different, and the specific parameter settings are shown in Table 3 below:
[0127] Table 3
[0128]
[0129] Other parameter conditions not shown are exactly the same as those in Example 1-1.
[0130] Experimental example
[0131] The lithium ion batteries obtained in the examples and comparative examples were subjected to cycle performance tests and short circuit safety tests, respectively.
[0132] 1. 0℃0.2C / 1C cycle performance test
[0133] The battery obtained in the embodiment and the comparative example was discharged at 0°C with a current of 1C to 3.0V, then charged at a constant current of 0.2C to a voltage of 4.25V, then charged at a constant voltage at 4.25V to a current of 0.05C, left to stand for 5 minutes, and then discharged at a constant current of 1C to a voltage of 3.0V. This is one charge and discharge cycle. The battery thickness was recorded, and the discharge capacity of the first week of the test was counted as x mAh, and the discharge capacity of the Nth week was counted as y mAh; the capacity of the Nth week was divided by the capacity of the first week to obtain the cycle capacity retention rate R=y / x of the Nth week, and the number of cycles when the battery capacity retention rate was 80% was recorded.
[0134] 2. 25℃ 0.2C / 1C cycle performance test
[0135] The battery obtained in the embodiment and the comparative example was discharged at 25°C at a current of 1C to 3.0V, then charged at a constant current of 0.2C to a voltage of 4.25V, then charged at a constant voltage at 4.25V to a current of 0.05C, left to stand for 5 minutes, and then discharged at a constant current of 1C to a voltage of 3.0V. This is a charge and discharge cycle. The battery thickness was recorded, and the discharge capacity of the first week of the test was calculated as xmAh, and the discharge capacity of the Nth week was calculated as ymAh; the capacity of the Nth week was divided by the capacity of the first week to obtain the cycle capacity retention rate of the Nth week R=y / x, and the number of cycles when the battery capacity retention rate was 80% was recorded.
[0136] 3. 25℃ 0.5C / 3C cycle test
[0137] The battery obtained in the embodiment and the comparative example was discharged at 25°C at a current of 3C to 3.0V. Then it was charged at a constant current of 0.5C to a voltage of 4.25V, and then charged at a constant voltage at 4.25V to a current of 0.05C, left to stand for 5 minutes, and then discharged at a constant current of 3C to a voltage of 3.0V. This is a charge and discharge cycle. The discharge capacity of the first week of the test is x mAh, and the discharge capacity of the Nth week is y mAh; the capacity of the Nth week is divided by the capacity of the first week to obtain the cycle capacity retention rate R=y / x of the Nth week, and the number of cycles when the battery capacity retention rate is 80% is recorded.
[0138] 4. Battery short circuit safety test
[0139] The batteries obtained in the examples and comparative examples were discharged at 25°C at a current of 5C to 3.0V. Then they were charged at a constant current of 1C to a voltage of 4.25V, and then charged at a constant voltage of 4.25V to a current of 0.05C, left to stand for 5 minutes, and then discharged at a constant current of 5C to a voltage of 3.0V. This was a charge and discharge cycle. During the cycle, if the voltage value suddenly dropped, especially from a normal value to a level close to zero, it indicated that a short circuit occurred inside the battery. Record whether the battery had thermal runaway, fire or explosion when the battery was short-circuited.
[0140] The results obtained from the above-mentioned Examples 1-3 are shown in Tables 4 to 6 below.
[0141] Table 4
[0142]
[0143]
[0144] Table 5
[0145] 0℃0.2C / 1C cycle / T 25℃0.2C / 1C cycle / T 25℃0.5C / 3C cycle / T Short circuit safety pass rate Example 2-1 389 578 520 10 / 10 Example 2-2 391 581 523 10 / 10 Example 2-3 390 580 521 10 / 10 Embodiment 2-4 393 583 525 10 / 10 Embodiment 2-5 389 571 523 9 / 10 Embodiment 2-6 382 565 514 10 / 10 Embodiment 2-7 371 556 502 10 / 10 Embodiment 2-8 392 581 523 10 / 10 Embodiment 2-9 387 577 518 10 / 10 Embodiment 2-10 374 562 503 10 / 10 Example 2-11 379 568 505 8 / 10 Example 2-12 370 561 496 9 / 10 Example 2-13 363 555 490 10 / 10 Example 2-14 388 573 515 10 / 10 Example 2-15 391 578 520 10 / 10 Example 2-16 390 575 526 10 / 10 Example 2-17 386 570 513 10 / 10 Example 2-18 386 577 520 10 / 10 Example 2-19 385 575 518 10 / 10 Comparative Example 2-1 335 499 453 6 / 10 Comparative Example 2-2 328 491 445 5 / 10
[0146] Table 6
[0147]
[0148]
[0149] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.
Claims
1. A lithium metal battery, comprising an electrolyte, a separator, a positive electrode sheet, and a negative electrode sheet, characterized in that: The electrolyte includes compound A and compound B; The mass proportion of the compound A in the electrolyte is a%, and a satisfies: 5≤a≤50; The mass proportion of the compound B in the electrolyte is b%, and b satisfies: 5≤b≤50; The liquid retention coefficient of the lithium metal battery is zg / Ah, and z satisfies: 1.5≤z≤2.2; The compound A comprises at least one of the structures shown in Formula 1, Wherein, R1 and R2 are independently selected from H, halogen, halogen-substituted or unsubstituted hydrocarbon group with 1 to 6 carbon atoms, and hydrocarbonoxy group; The compound B comprises at least one of the structures shown in Formula 2, Wherein, R3 and R4 are independently selected from H, F substituted or unsubstituted hydrocarbon groups and hydrocarbonoxy groups with 1 to 10 carbon atoms, and at least one of R3 and R4 contains F.
2. The lithium metal battery according to claim 1, characterized in that The compound A includes at least one of the following structural formulas 1-1 to 1-8: And / or, the compound B comprises at least one of the following structural formulas 2-1 to 2-8:
3. The lithium metal battery according to claim 1, characterized in that The lithium metal battery satisfies: 13≤(a+b) / z≤40.
4. The lithium metal battery according to any one of claims 1 to 3, characterized in that: The electrolyte further includes a compound F, wherein the compound F includes at least one of the structures shown in Formula 3, Wherein, R5 and R6 are independently selected from a hydrocarbon group or a hydrocarbonoxy group having 1 to 10 carbon atoms; Preferably, compound F accounts for f% of the total mass of the electrolyte, and f satisfies: 10≤f≤20; Preferably, the compound F comprises at least one of the following structural formulas 3-1 to 3-8:
5. The lithium metal battery according to claim 4, characterized in that The diaphragm comprises a base layer and a glue layer arranged on the surface of the base layer; the thickness of the glue layer is d μm, 0.5≤d≤8.
6. The lithium metal battery according to claim 5, characterized in that The base layer includes a substrate layer and a ceramic layer located on one side or both sides of the substrate layer; Preferably, the thickness of the ceramic layer is e μm, and e satisfies: 0<e≤8.
7. The lithium metal battery according to claim 6, characterized in that The ceramic layer includes inorganic particles, the particle size of the inorganic particles is g μm, and g satisfies: 0.1≤g≤1.5; And / or, the porosity of the diaphragm is h%, and h satisfies: 30≤h≤50.
8. The lithium metal battery according to any one of claims 1 to 3, characterized in that: The electrolyte also contains a phosphorus-containing compound; Preferably, the phosphorus-containing compound accounts for i% of the total mass of the electrolyte, and i satisfies: 0.1≤i≤20; Preferably, the phosphorus-containing compound is selected from at least one of LiPO2F2, tris(2,2,2-trifluoroethyl) phosphate, triphenyl phosphate, ethoxypentafluorocyclotriphosphazene, triphenyl phosphine oxide, triphenyl phosphine, p-toluoyl phosphate, and toluene diphenyl phosphate.
9. The lithium metal battery according to any one of claims 1 to 3, characterized in that: The electrolyte also includes a nitrogen-containing compound; Preferably, the nitrogen-containing compound accounts for j% of the total mass of the electrolyte, and j satisfies: 0.1≤j≤5; Preferably, the nitrogen-containing compound is selected from one or more of lithium nitrate, 2-fluoropyridine, pentafluoropyridine, 3-fluoropyridine, 2-trimethylsilylethynylpyridine, 1,2-bis(di-2-pyridylphosphine)ethane, 1-methylbenzotriazole, isopropyl nitrate, and 4-ethylpyridine.
10. The lithium metal battery according to any one of claims 1 to 9, characterized in that: The positive electrode sheet includes a positive electrode active material, and the positive electrode active material includes a ternary material; Preferably, the lithium metal battery is a laminated battery.
Citation Information
Patent Citations
Application of fluoro-ether solvent and electrolyte in energy storage battery
CN115051033A
Lithium metal battery and electronic device
CN116368656A
High-temperature-resistant flame-retardant double-salt lithium battery electrolyte as well as preparation method and application thereof
CN118198484A
Electrochemical device
WO2023213188A1